Evaporation‐Directed Crack‐Patterning of Metal–Organic Framework Colloidal Films and Their Application as Photonic Sensors. Issue 45 (6th October 2017) - Dalstein, Olivier; Gkaniatsou, Effrosyni; Sicard, Clemence; Sel, Ozlem; Perrot, Hubert; Serre, Christian; Boissière, Cédric; Faustini, Marco
Abstract: A straightforward crack‐patterning method is reported allowing the direct formation of periodic cracks in metal–organic framework (MOF) nanoparticle films during dip‐coating deposition. The crack propagation and periodicity can be easily tailored by controlling the evaporation front and the withdrawal speed. Several MOF‐patterned films can be fabricated on large surfaces and on several substrates (flat, curved or flexible) including the inner surface of a tube, not achievable by other lithographic techniques. We demonstrate that the periodic cracked arrays diffract light and, due to the MOF sorption properties, photonic vapor sensors are fabricated. A new concept of "in‐tube", MOF‐based diffraction grating sensors is proposed with outstanding sensitivity that can be easily tuned "on‐demand" as function of the desired detection range. Abstract : Photonic cracks : A dip‐coating method allowing simultaneous deposition and crack‐patterning of MOF colloidal films is demonstrated. The oriented periodic cracks arrays are tunable, act as diffraction gratings and can be fabricated on complex surfaces. A new concept of MOF‐based vapor sensors is proposed in which the sensitivity range can be tuned on‐demand.